Total Ionizing Dose and Single Event Effect Radiation effects in SiC SCT10N120 Power MOSFET - Rajendran, Vishandh (2018)
Silicon Carbide Power MOSFET is type of high power switching device which is used in the space application, avionics and military applications. Silicon Carbide Power MOSFFETs are much favorable nowadays not only because of its fast switching capabilities and amplifying capabilities but also due to its high Voltage and current handling capacity. At the space, the power MOSFETs are used in satellites for DC-DC converters such as buck converter or boost converter. These type converters provide stepup or step-down in DC voltage for the satellites. But due to the harmful radiation on the surrounding such as the outer space, these Power MOSFETs gets exposed and tends to perform poorly. The longer the exposure the higher the effect on the Power MOSFET. Sometimes single charged particle can cause the Power MOSFET to completely fail from performing.